Urgensi Pembentukan Peraturan Daerah tentang Penanganan Satwa Liar dalam Persfektif Otonomi Daerah di Kabupaten Indragiri Hilir - Jamri; Muhsin; Wandi (Indra Institute Research & Publication, 2025)
Conflicts between local communities and wildlife in Indragiri Hilir Regency have become increasingly frequent, primarily due to habitat encroachment and the expansion of human activities into forested and swamp areas. Unfortunately, there is currently no regional legal product that specifically regulates the mechanisms for handling such conflicts. As a result, local agencies—such as the Fire and Rescue Department—face operational limitations due to a lack of authority and legal basis. This study aims to analyze the authority of regional governments in addressing human-wildlife conflicts based on the principles of regional autonomy and to examine the urgency of establishing a Regional Regulation (Perda) as a legitimate and operational legal framework. Using a normative juridical method with a statutory and conceptual approach, the research reveals a normative gap that weakens legal protection for the community and hinders the effectiveness of local institutions. Therefore, the formulation of a Regional Regulation that outlines prevention, mitigation, and coordination mechanisms for managing wildlife conflicts is urgently needed to ensure public safety and strengthen the role of local governments in environmental protection.